Energy Related Issues for MANETs: A Study - Kishore, Nand; Singh, Sukhvir; Dhir, Renu (International Journal of Computer Sciences and Engineering, 2014)
Energy efficient Routing is one of the keyissues in MANETs due to their highly dynamic topology and limited battery power at the nodes. In particular identifying energy efficient routing is the most important parameters for mobile ad-hoc networks. Power failure of a mobile node not only affects the node itself but also reduces the overall network lifetime. The goal of this paper is to facilitate research efforts in combining existing solutions in order to offer a more energy efficient routing approach. Towards this goal, we analysed of the three routing protocols AODV, DSR and DSDV for mobile ad-hoc networks scenarios. Our study mainly the energy consumed by each protocol.